A novel double-effect compression-assisted absorption thermal battery with high storage performance for thermal energy storage. (May 2022) - Ding, Zhixiong; Wu, Wei
Abstract: Thermal battery plays a key role in increasing the utilization of renewable energy. The absorption thermal battery stands out due to its better comprehensive performance and higher application flexibility. However, the energy storage efficiency and density still need improvement, and the performance attenuation in the discharging process also needs mitigation. Thus, a novel double-effect compression-assisted absorption thermal battery is proposed in this study. The dynamic characteristics and storage performance of the novel cycle are compared with various absorption thermal battery cycles using a validated dynamic model. Results indicate that the novel cycle recovers the condensation heat like the basic double-effect cycle, which leads to an increase in energy storage efficiency. Besides, strengthened and modulated by the auxiliary compression, the energy storage density is enhanced, the charging temperature is lowered, and the discharging rate is stabilized. Under a charging temperature of 130 °C, the energy storage efficiency and density of the novel cycle are enhanced from 1.00 to 1.24 and 94.6 kWh/m 3 to 240.0 kWh/m 3, compared with the double-effect cycle without compression. This paper aims to provide theoretical references and suggestions for the advancement of absorption thermal batteries. Highlights: A novel double-effect compression-assisted absorption thermal battery is proposed. Energy storage efficiency and density are significantly enhanced by 24% and 145%. The discharging rate is stabilized with the assistance of compression. Comparative studies among 8 absorption-based thermal battery cycles are conducted.